UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN POBLEM SOLVING PADA MATERI RELASI KELAS VIII - Valensia Ose; Natalia Peni; Maria Fatima Mei (Program Studi Pendidikan Matematika, 2021)
The purpose of this study was to determine student activities, teacher activities, and learning outcomes through problem-solving learning on the relationship material of class VIII SMPN 2 Adonara Barat. This research is classroom action research. The research subjects were students of class VIII SMPN 2 Adonara Barat, totalling 16 people. Data collection is done by observation, tests, and documentation. The data analysis technique used is quantitative data analysis. The results showed that learning mathematics using problem-solving can improve student and teacher activities and student learning outcomes. Based on the results of data analysis, the level of implementation of teacher activities in the first cycle was 75% with good criteria, in the second cycle, it was 93,1% with very good criteria. For student activities in the first cycle of 65% with sufficient criteria and the second cycle of 84% with good criteria. Student learning outcomes have increased learning mastery with a pre-action percentage of 6.25%, the first cycle of 31.25%, and the second cycle of 100% learning outcomes. The increase in the average value of the pre-test results was 42.25%, the first cycle was 65% and the second cycle was 82.25%.